The emerging frontier: gangs in developing countries - Covey, Herbert C. (The Oxford handbook of gangs and society, 2024)
This chapter proposes that gang research in developing countries should expand. Over the next decades, developing countries will experience demographic changes that will provide fertile grounds for the formation and expansion of gangs, such as population growth, urbanization, and migration. In addition, cultural and historical contexts and processes in developing countries, such as colonization and civil conflicts, differ from the developed world, where most gang research has been conducted. This chapter encourages an assessment of the applicability of existing concepts to gangs in developing countries. Undoubtedly, some current concepts and approaches are directly applicable to understanding gangs in developing countries, but others may need modification. Given the wide variety of cultures, ethnicities, and contexts in the developing world, the definition of “gang” needs to be at the forefront of discussion. Other subjects, such as the drug trade, migration of populations, marginalization, and gang evolution, need to be assessed for applicability.